TNFAIP3 alleviates cerebral ischemia-reperfusion injury by inhibiting M1 microglia polarization via deubiquitination of RACK1 - Wenya Bai; Shixuan Liu; Guilin Zhou; Xuelian Li; Huan Jiang; Jianlin Shao; Junchao Zhu (PLoS ONE, 2025)
Background Microglia polarization plays a crucial role in the progression of cerebral ischemia-reperfusion injury (CIRI), but the mechanisms remain largely undefined. The preset study aimed to investigate the mechanism of microglia polarization following CIRI. Methods CIRI was modeled in C57BL/6J mice through middle cerebral artery occlusion-reperfusion and in BV2 cells via oxygen and glucose deprivation/reoxygenation. Reverse transcription-quantitative PCR, western blotting, flow cytometry and fluorescence staining were used to detect the expression levels of key proteins associated with microglia polarization, as well as the expression of TNFAIP3 and RACK1. The interaction between TNFAIP3 and RACK1 was verified by co-immunoprecipitation. TNFAIP3 or RACK1 gene interference (overexpression and/or silencing) was employed to examine the role of the TNFAIP3/RACK1 axis in microglia polarization following CIRI. Results The results revealed that Arg-1 expression decreased, inducible nitric oxide synthase expression increased and TNFAIP3 was upregulated 24 h after CIRI. Furthermore, TNFAIP3 interacted with RACK1 to deubiquitinate and increase the expression of RACK1. These results indicate that knocking down either TNFAIP3 or RACK1 promotes microglia M1 polarization, and overexpression of RACK1 can promote microglia M2 polarization. RACK1 exerts its neuroprotective effects through NF-κB, as demonstrated by the use of NF-κB inhibitors. Conclusion The present findings indicate that TNFAIP3 inhibits M1 microglial polarization via deubiquitination of RACK1 after CIRI, RACK1 exerts its effects through NF-κB.